When trade saves natural resources: Evidence from cereals trade in SADC - Traoré, Fousseini; Matchaya, Greenwell C.; Garcia, Roberto J. (International Food Policy Research Institute, 2025)
Africa is one of the continents most vulnerable to climate change. While global temperatures have risen by 0.2°C per decade since 1991, Africa has registered a 0.3°C increase (WMO, 2022). Beyond rising temperatures, Africa faces various related challenges, including rising sea levels, unpredictable rainfall leading to both droughts and severe storms, and increased threats from plant pests and animal diseases. As a result, the continent is expected to see a significant decline in arable land, further compromising its agricultural future. Specifically, southern Africa is highly climate vulnerable. Water scarcity is critical for food security, yet trade can help reallocate cereals from water-rich to water-scarce areas.